2020
DOI: 10.1155/2020/2803496
|View full text |Cite
|
Sign up to set email alerts
|

Erchen Plus Huiyanzhuyu Decoction Inhibits the Growth of Laryngeal Carcinoma in a Mouse Model of Phlegm‐Coagulation‐Blood‐Stasis Syndrome via the STAT3/Cyclin D1 Pathway

Abstract: Erchen plus Huiyanzhuyu decoction (EHD), a Chinese herbal medicine (CHM) formula that consists of Erchen decoction and Huiyanzhuyu decoction, has achieved satisfactory results in the clinic. The main function of EHD is to remove phlegm and blood stasis, and EHD is suitable for phlegm-coagulation-blood-stasis (PCBS) syndrome in laryngeal cancer (LC). In this study, a xenograft mouse model of LC with PCBS syndrome was constructed by feeding a high-fat diet, swimming in ice water, and subcutaneously injecting epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Taken collectively, the data suggest that ECD is an efective lipid-lowering compound that acted by regulating fatty acid metabolism. Te antitumor efects of ECD in combination with Huiyan Zhuyu decoction have been established in laryngeal carcinomas [21,22]. ECD has also been used therapeutically for chronic bronchitis [23].…”
Section: Discussionmentioning
confidence: 99%
“…Taken collectively, the data suggest that ECD is an efective lipid-lowering compound that acted by regulating fatty acid metabolism. Te antitumor efects of ECD in combination with Huiyan Zhuyu decoction have been established in laryngeal carcinomas [21,22]. ECD has also been used therapeutically for chronic bronchitis [23].…”
Section: Discussionmentioning
confidence: 99%
“…ECD is the common TCM that originated from the Taiping Huimin Formula Bureau and has been widely applied in the treatment of obesity, hyperlipidemia, diabetes, and other diseases caused by metabolic disorders ( Gao et al, 2015 ; Ding et al, 2018 ; Zhang et al, 2020a ; Zhao et al, 2021 ). Considering the remarkable metabolic regulation effects of ECD, recent studies indicated that ECD could inhibit tumorigenesis and promote the apoptosis of laryngeal squamous cell carcinoma cells ( Tan et al, 2020 ; Zhou et al, 2020 ). While some clinical studies showed ECD could be utilized as adjuvant therapy for patients with advanced CRC ( Mei et al, 2016 ; Zhou et al, 2021 ), the anti-tumor effects and mechanisms of ECD on CRC have not been systematically determined.…”
Section: Discussionmentioning
confidence: 99%
“…The study, performed by our team, has found that one of the potential mechanisms of ECD is regulating the expression of PPARγ and LPL, and some other metabolism-related molecules ( Zhang et al, 2020a ). Recently, the team of Xi Tan has reported that ECD inhibits the growth of laryngeal carcinoma via the STAT3/Cyclin D1 pathway and it was the first study on the mechanism of ECD in the treatment of tumors ( Tan et al, 2020 ). In the current study, based on the results of key targets and pathways analysis, we speculated the underlying molecular mechanisms of ECD in the treatment of CRC are likely to be related to tumor immune and tumor metabolism in TME.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some Chinese herbs have been frequently utilized for the treatment of different diseases, such as cardiovascular diseases, diabetes and caners [ 8 10 ]. A recent research highlights that erchen plus huiyanzhuyu decoction can inhibit the growth of laryngeal carcinoma by modulating STAT3/cyclin D1 signaling pathway [ 11 ]. TCM exerts promising therapeutic effect on various malignant tumors.…”
Section: Introductionmentioning
confidence: 99%